1988
DOI: 10.1148/radiology.169.1.3420242
|View full text |Cite
|
Sign up to set email alerts
|

Normal perivascular spaces mimicking lacunar infarction: MR imaging.

Abstract: Perivascular (Virchow-Robin) spaces normally surround perforating arteries that enter the medial temporal lobes, corpus striatum, and thalamus. The high soft-tissue sensitivity of magnetic resonance (MR) imaging allows for the frequent detection of such cerebrospinal fluid (CSF)-filled spaces. Especially on axial images, these CSF-filled perivascular spaces may be confused with pathologic lesions, such a lacunar infarcts. Postmortem brain specimens demonstrate the anatomy of perivascular spaces around perforat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
7

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 0 publications
0
59
0
7
Order By: Relevance
“…Indeed, PVS are correlated with increasing age, 4,9,13 though some earlier studies have shown equal distribution of PVS through a range of ages. 14,15 In addition, a sex difference in the distribution of PVS in the basal ganglia has been reported, with men having more PVS than women. 11,13,16 The most common etiologies proposed for the widening of the originally virtual PVS to become visible on MR imaging are hypertension 13,17 and amyloid deposition, at least in patients with Alzheimer disease.…”
mentioning
confidence: 99%
“…Indeed, PVS are correlated with increasing age, 4,9,13 though some earlier studies have shown equal distribution of PVS through a range of ages. 14,15 In addition, a sex difference in the distribution of PVS in the basal ganglia has been reported, with men having more PVS than women. 11,13,16 The most common etiologies proposed for the widening of the originally virtual PVS to become visible on MR imaging are hypertension 13,17 and amyloid deposition, at least in patients with Alzheimer disease.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging demonstrates enlarged perivascular spaces as tiny-to-large CSF-filled cavities with well-defined smooth margins that are surrounded by normal brain parenchyma and display no enhancement after administration of contrast agent. [11,17] The typical distribution of the perivascular spaces visible on MR imaging includes the basal ganglia, the cerebral white matter, and the midbrain, conforming to the path of the penetrating arteries. In particular, in 20% of patients in whom MR imaging was performed, tiny perivascular spaces were identified at the junction of the substantia nigra and cerebral peduncle, where the penetrating branches of the collicular or accessory collicular arteries are located.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging enables an in vivo demonstration of expanding lacunae and contributes to their differential diagnosis, which includes other brain cysts. [10,11,17] In the current report we describe two patients in whom mesencephalothalamic expanding lacunae were observed on MR imaging and in whom the referring complaints were related to triventricular hydrocephalus that was caused by obstruction and stenosis of the cerebral aqueduct and compression of adjacent brain parenchyma. …”
mentioning
confidence: 89%
“…Recently, several authors have raised the following differential points: lacunae occur in the upper two-thirds of the basal ganglia, are slit-like or ovoid in shape, and are larger than 5 mmin size. Dilated Virchow-Robin spaces locate in the inferior one-third of the putamen, their morphology is round or linear, and they are usually 5 mmor less (13,14). In addition, Virchow-Robin spaces are more symmetric and bilateral than lacunae (15).…”
Section: Discussionmentioning
confidence: 99%